The role and economics of immunotherapy in solid tumour management. (December 2020) - Worku, Dominic Adam; Hewitt, Victoria
Cancer therapeutics is a rapidly changing field which offers patients the prospect of a better quality of life and cure. Immunotherapy has become a unique approach for select metastatic solid tumours. While initial results do show durable responses in select patients, there are concerns on how best to utilise this expensive resource which can result in costly side effects and in whom the use of biomarkers to stratify patients is still in its infancy. Given the ageing population and extreme challenges on healthcare, economic modelling with regards to immunotherapy is imperative especially now when it is being considered for further cancer types.